"Calix[4]-box" cages promote the formation of amide bonds in water in the absence of coupling reagents. Issue 70 (18th July 2018) - Feng, Wei-Xu; Dai, Liya; Zheng, Shao-Ping; van der Lee, Arie; Su, Cheng-Yong; Barboiu, Mihail
Abstract : Calix[4]box cages promote template synthesis via accelerated amide bond formation upon encapsulation in water. Abstract : The present work shows that encapsulation can be used to promote amide bond formation in water under mild conditions, in the absence of carbodiimide coupling agents.